Trauma Resuscitation Evaluation Times and Correlating Human Patient Simulation Training Differences—What is the Standard?. Issue 11 (1st November 2016) - Bonjour, Timothy J.; Charny, Grigory; Thaxton, Robert E.
ABSTRACT: Background: Rapid effective trauma resuscitations (TRs) decrease patient morbidity and mortality. Few studies have evaluated TR care times. Effective time goals and superior human patient simulator (HPS) training can improve patient survivability. Objectives: The purpose of this study was to compare live TR to HPS resuscitation times to determine mean incremental resuscitation times and ascertain if simulation was educationally equivalent. The study was conducted at San Antonio Military Medical Center, Department of Defense Level I trauma center. Design and Methods: This was a prospective observational study measuring incremental step times by trauma teams during trauma and simulation patient resuscitations. Trauma and simulation patient arms had 60 patients for statistical significance. Participants included Emergency Medicine residents and Physician Assistant residents as the trauma team leader. Results: The trauma patient arm revealed a mean evaluation time of 10:33 and simulation arm 10:23. Comparable time characteristics in the airway, intravenous access, blood sample collection, and blood pressure data subsets were seen. Conclusions: TR mean times were similar to the HPS arm subsets demonstrating simulation as an effective educational tool. Effective stepwise approaches, incremental time goals, and superior HPS training can improve patient survivability and improved departmental productivity using TR teams.